2009
DOI: 10.1071/mf08339
|View full text |Cite
|
Sign up to set email alerts
|

Target setting for pollutant discharge management of rivers in the Great Barrier Reef catchment area

Abstract: Abstract. Water Quality Improvement Plans (WQIPs) are being developed for individual river basins on the Great Barrier Reef (GBR) catchment associated with the GBR Water Quality Protection Plan. Within each WQIP, marine ecosystem targets are linked to end-of-river pollutant (suspended sediments, nutrients and pesticides) load targets and to farm level management practice targets. The targets are linked through quantitative models; e.g. one model connects GBR chlorophyll concentrations (marine target) to end-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 53 publications
0
47
0
Order By: Relevance
“…Total P export was ∼1/10 of the TN export and mostly from particulate P (65%), which illustrates the importance of sediment control from fertilised cropping lands. However, while a reduction of 25% in DIN loads by the sugarcane and banana industries may be readily achievable, Brodie et al (2009) have reported that a reduction of 80% may be needed in the Tully-Murray to meet target chlorophyll loads in the marine environment. They discuss the implications of this disparity.…”
Section: Discussionmentioning
confidence: 99%
“…Total P export was ∼1/10 of the TN export and mostly from particulate P (65%), which illustrates the importance of sediment control from fertilised cropping lands. However, while a reduction of 25% in DIN loads by the sugarcane and banana industries may be readily achievable, Brodie et al (2009) have reported that a reduction of 80% may be needed in the Tully-Murray to meet target chlorophyll loads in the marine environment. They discuss the implications of this disparity.…”
Section: Discussionmentioning
confidence: 99%
“…This is a critical finding because aquatic ecosystem values require the most stringent WQOs. This finding has also been important because targets for pollutant discharge of rivers to the Reef are being set linking marine ecosystem objectives to end-of-basin pollutant load objectives (Brodie et al 2009). Both objectives, marine and end-of-basin, are most likely to match if the most stringent terrestrial WQOs are set and supported by farmers and industry.…”
Section: Community Uses and Values Of Water In The Tully Basinmentioning
confidence: 99%
“…Contemporary estimates suggest that the total nitrogen discharge to the GBR has increased from 14,000 tonnes year -1 in pre-development times (prior to 1850) to a current discharge of 58,000 tonnes year -1 ; a four-fold increase (Brodie et al 2009a). The predominant form of the nitrogen that is delivered to the GBR has also changed.…”
Section: Nutrient Supply To Gbr Marine Watersmentioning
confidence: 96%